Haemophilus influenzae and oxidative stress - Harrison, Alistair; Bakaletz, Lauren O.; Munson, Robert S. (Frontiers in Cellular and Infection Microbiology, 2012)
Haemophilus influenzae is a commensal of the human upper respiratory tract. H. influenzae can, however, move out of its commensal niche and cause multiple respiratory tract diseases. Such diseases include otitis media in young children, as well as exacerbations of chronic obstructive pulmonary disease, sinusitis, conjunctivitis and bronchitis. During the course of colonization and infection, H. influenzae must withstand oxidative stress generated by multiple reactive oxygen species produced endogenously, by other co-pathogens and by host cells. H. influenzae has therefore evolved multiple mechanisms that protect the cell against oxygen-generated stresses. In this review, we will describe these systems. Moreover, we will compare how H. influenzae obviates the effect of oxidative stress as a necessary phenotype for its roles as both a successful commensal and pathogen, relative to the well-described systems in Escherichia coli.